HEALTH WORKER AND CAREGIVER INTERACTION DURING CHILD VACCINATION SESSIONS AT HEALTH FACILITIES IN SOMALI REGION OF ETHIOPIA: A QUALITATIVE STUDY - Samuel TESHOME (Rojan GÜMÜŞ, 2020)
Somali Region is one of the largest region in Ethiopia which has performed persistently low with immunization coverage. communication during vaccination sessions at health facilities is one of the key factors that influence caregiver's decision to bring back their children for vaccination. The Objective of this study was to evaluate health worker and caregiver interaction during immunization session and identify communication gaps in Somali region Material and Methods: This was a cross sectional qualitative study. The study was carried out using in depth interview with health workers responsible for vaccination, observation of vaccinator and caregiver interaction during immunization session and exit interview of caregivers who brought their children for vaccination or whose child was vaccinated at the health facility. Results: Health workers responsible for vaccination in twelve health facilities from central and remote part of the region were interviewed. A total of 63 vaccination sessions in the 12 health facilities were observed and caregivers were interviewed on exit. Most caregivers described the vaccinators as friendly and supportive. Some mothers who did not bring the immunization card with them were returned with out child getting the service. The return date for vaccination was written on immunization card in most cases. Most caregivers do not identify vaccines by name or purpose, however they all want their children get all vaccines as recommended by health workers. Conclusion Health worker do not communicate required information for continued use of immunization service at health facilities during vaccination session. caregiver interaction in Somali region will need to be improved though training of health workers on immunization basics and communication